Case study of hydraulic fracturing for coal burst risk mitigation - Hongpu Kang; Yongxue Xia; Meihua Feng; Chuang Lu; Fuqiang Gao (International Journal of Coal Science & Technology)
Abstract Coal bursts pose significant safety and operational challenges in deep mining environments, necessitating effective mitigation strategies to address high-stress concentrations and dynamic failure risks. This study evaluated the efficacy of hydraulic fracturing as a preconditioning tool at a longwall face of the Mengcun coal mine with strong coal bursts, Shaanxi Province. The program involved the systematic creation of a fracture network through high-pressure fluid injection, monitored via microseismic arrays, stress measurements, and hydrological sensors. Results demonstrated that hydraulic fracturing effectively redistributed in-situ stresses, reducing high-stress concentrations by up to 30%, lowering the frequency of high-energy microseismic events, and enhancing the stability of fractured zones. However, the presence of unfractured blind spots and interactions with pre-existing faults highlighted the need for optimized well placement and adaptive fracturing designs. These findings underscore the potential of hydraulic fracturing as a critical preconditioning tool in high-stress mining operations, which could provide a framework for improving safety and efficiency in similar geological and operational settings.